Impact of Zn\(^2+\) and Selenite on Rat Ascites Hepatoma AS-30D Cells and Rat Liver Mitochondria: A Comparison with Cd\(^2+\), Hg\(^2+\), Cu\(^2+\), and Ca\(^2+\) - Elena A. Belyaeva (Recent Developments in Chemistry and Biochemistry Research Vol. 10, 2025)
The objective of this work was to study the molecular mechanisms of metal/metalloid cytotoxicity using Zn2+ and sodium selenite (Na2SeO3) and compare them at the cellular and mitochondrial levels. For this, we used rat ascites hepatoma AS-30D cells and rat liver mitochondria, as well as flow cytometry, spectrofluorometry, polarography and ion-selective electrode technique. Mitochondria of AS-30D cells were found to be a major target for both Zn2+ and selenite. High [mu]M concentrations of Zn2+ or selenite were highly cytotoxic and killed these cells by both apoptotic and necrotic pathways. Both Zn2+ and selenite induced significant changes in the intracellular generation of reactive oxygen species (ROS) and caused mitochondrial dysfunction through disturbance of the mitochondrial electron transport chain (mtETC), dissipation of mitochondrial membrane potential, and opening of mitochondrial permeability transition pores. Significant differences were revealed in the toxic effects of Zn2+ and selenite on both AS-30D cells and isolated rat liver mitochondria. In particular, selenite caused a significantly higher level of intracellular ROS production (an early cellular event) compared to Zn2+, but a lesser membrane potential loss and a smaller decrease in the rate of maximal (fully uncoupled) cellular respiration, while mtETC disturbance was a early and key event in the mechanism of Zn2+ cytotoxicity. Importantly, the data found on cells were in good agreement with those obtained on isolated mitochondria. In addition, the sequence of events manifested in the mitochondrial dysfunction induced by the tested metal/metalloid was compared with that for Cd2+, Hg2+, Cu2+, and Ca2+ on the same model system. As a consequence, the molecular mechanisms of the metal/metalloid toxicity have been elucidated, highlighting differences in their action on mitochondrial function and cell fate and providing a rationale for the combined use of such compounds in various therapeutic strategies, including anticancer and many others.